Combined Tevatron upper limit on gg→H→W+W- and constraints on the Higgs boson mass in fourth-generation fermion models - Aaltonen, T. (2010)
We combine results from searches by the CDF and D0 collaborations for a standard model Higgs boson (H) in the process gg→H→W+W - in pp̄ collisions at the Fermilab Tevatron Collider at √s=1.96TeV. With 4.8fb-1 of integrated luminosity analyzed at CDF and 5.4fb-1 at D0, the 95% confidence level upper limit on σ(gg→H)×B(H→W+W-) is 1.75 pb at mH=120GeV, 0.38 pb at mH=165GeV, and 0.83 pb at mH=200GeV. Assuming the presence of a fourth sequential generation of fermions with large masses, we exclude at the 95% confidence level a standard-model-like Higgs boson with a mass between 131 and 204 GeV. © 2010 The American Physical Society.